Total Thoracoscopic versus Robotic Surgery for Repair of Atrial Septum Defect: A Propensity Matching Score Analysis - Yanyi Liu; Zhuang Liu; Xin Li; Ning Li; Ruirui Kong; Yiyao Jiang; Shenglin Ge; Chengxin Zhang (Emergency Medicine International, 2022)
Robotic surgery can provide less surgical trauma than conventional surgery, but differences between robotic and thoracoscopic surgery for atrial septal defect (ASD) repair are not well documented. To explore whether ASD can be repaired by thoracoscopic surgery or robotic surgery, which procedure is less invasive, and the difference in outcomes between these two procedures, this article studies 160 patients undergoing ASD repair at our institution. Sixty-five patients underwent total thoracoscopic surgery and 95 patients underwent total endoscopic robotic surgery. Propensity score matching yielded 64 well-matched patient pairs. Surgical data and early postoperative outcomes between the two matched groups were analyzed and compared. The results show that thoracoscopic and robotic surgery to repair ASD are both safe and reliable, and the early curative effect is good. However, regardless of similar complication rates, robotic surgery has a shorter time, less postoperative drainage, and faster recovery than thoracoscopic surgery.